Improving Inventory Management Efficiency Through the Reduction of Stock Discrepancies Using a Lean-6S Framework Based on the DMAIC Method - Andika Mumtaza; Isti Surjandari (International Journal Labs, 2026)
Effective inventory management is a critical factor in ensuring operational continuity and efficiency in manufacturing companies. However, many organizations still experience inventory inaccuracies caused by stock discrepancies, improper material placement, inadequate storage standards, and ineffective control systems. This study aims to improve inventory management efficiency by implementing a digitized 6S framework integrated with the DMAIC (Define, Measure, Analyze, Improve, Control) method to reduce stock discrepancies in a printer manufacturing company in Indonesia. The research employed a quantitative approach supported by qualitative descriptive analysis using a case study design. Data were collected through direct observation, interviews, documentation analysis, 6S audits, stock discrepancy measurements, material search time assessments, and safety condition evaluations. The results showed that the implementation of digitized 6S successfully reduced average stock discrepancies from 35.53% to 29.70% and increased inventory accuracy from 64.5% to 70.3%. Furthermore, material search time decreased from 150 minutes to 60 minutes, misplacement cases declined from 56 to 23 cases, and unsafe condition findings decreased from 19 to 6 findings. These findings indicate that the integration of digital control systems, workplace standardization, and lean improvement practices can enhance inventory accuracy, operational efficiency, and warehouse safety. In conclusion, digitized 6S based on DMAIC provides an effective and sustainable approach for reducing stock discrepancies and improving inventory management performance in manufacturing environments.